Analysis of the distribution of stress and deformation in single implant-supported prosthetic units in implants of different diameters - Francesco Salvatore MANNARINO; Carlos Eduardo FRANCISCHONE JÚNIOR; Renato Savi de CARVALHO; Bruno Salles SOTTO-MAIOR; Carlos Eduardo FRANCISCHONE
Abstract Introduction When stress and strain levels in the bone-implant system exceed It's capacity, a mechanical fatigue occurs, resulting in collapse and loss of osseointegration. Objective Analyze biomechanical behavior in single implant-supported prosthesis with implants of different diameters in the posterior mandible. Material and method Three different finite element models of Cone-Morse implants with the same height were created, varying the diameter (3.3 mm, 4.1 mm and 4.8 mm). The mandibular first molar area was the location of the implant, with It´s component and overlying prosthetic crown. The jawbone was composed of cortical and cancellous bone. Refined mesh of 0.5 mm was created in the critical interfaces to be analyzed. The loading of the models was performed at the point of occlusal contact with an occlusal load of 400 N. Result Maximum stress and strain occurred in the cervical regions of the implants in all groups, either in the implants or in components as well as in the analysis of cortical bone. The greater the diameter, the lower the stress and strain found in the implant. The 3.3 mm group had the highest strain in peri-implant cortical bone, and the 4.1 mm group had the smallest deformation, significantly lower than in the 4.8 mm group. Conclusion Although the biggest implant diameter (4.8 mm) appears to have lower values of stress and strain, the group of intermediate implant diameter (4.1 mm) showed less deformation rate in the cortical peri-implant bone. Therefore it is concluded that the 4.1 mm implant platform presented a more biomechanically effective peri-implant bone maintenance.